1995
DOI: 10.1016/0093-691x(95)00280-l
|View full text |Cite
|
Sign up to set email alerts
|

Viability of cloned bovine embryos after one or two cycles of nuclear transfer and in vitro culture

Abstract: We described an exclusively in vitro procedure for cloning and recloning bovine embryos. Embryos obtained by IVM/IVF/IVC developed to the morula stage were used as blastomere donors in cunjunction with IVM recipient oocytes. Reconstructed embryos were developed in vitro in co-culture using bovine oviductal epithelial cells. The resulting morulae were used as donors for recloning under the same experimental conditions. No significant difference was observed between cloning and recloning in terms of development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Data on viability of such embryos and on their development into live calves are limited, however. The birth of calves has been reported for second-and third-generation NT embryos [4,12,30], but pregnancy rates seem to be dramatically reduced for third-generation NT embryos [43] and to our knowledge, no term calves have yet been reported for bovine embryos cloned past the fourth generation. In 1996, Takano et al [47] reported that NT blastocysts of the fifth generation were able to initiate pregnancy when transferred to recipients but resulted in abortion.…”
Section: Multiple Generational Embryo Cloningmentioning
confidence: 97%
“…Data on viability of such embryos and on their development into live calves are limited, however. The birth of calves has been reported for second-and third-generation NT embryos [4,12,30], but pregnancy rates seem to be dramatically reduced for third-generation NT embryos [43] and to our knowledge, no term calves have yet been reported for bovine embryos cloned past the fourth generation. In 1996, Takano et al [47] reported that NT blastocysts of the fifth generation were able to initiate pregnancy when transferred to recipients but resulted in abortion.…”
Section: Multiple Generational Embryo Cloningmentioning
confidence: 97%
“…Ectors et al [26] reported 12.9% and 14.9% of blastocysts and 20% newborn in two rounds of NT from morulae. Takano et al [21] obtained 20%-37% of blastocysts in three NT series and 25% offspring (two calves) in the third series.…”
Section: Efficiency Of Serial Cloningmentioning
confidence: 97%
“…After two rounds of NT, 21 morulae and blastocysts were obtained [26], and after three rounds, 54 morulae from two single embryos [6] and 43 blastocysts from a single embryo [21] were produced. However, the yield of successfully developed embryos in serial NT experiments is still limited by the availability of recipient oocytes and by the number of scientists simultaneously performing NT rather than by biological efficiency of the system employed.…”
Section: Efficiency Of Serial Cloningmentioning
confidence: 99%
“…Isolated blastomeres from multicellular embryos still possess developmental capacity in vitro to progress to the blastocyst stage. Successful nuclear transfer in amphibians, fish, sheep, cattle, swine and rabbits have been accomplished by transfer of a blastomere from a pre‐implantation stage embryo into an enucleated oocyte with large‐scale multiplication achieved by serial repetition of the procedure using blastomeres from nuclear transfer embryos (Willadsen 1986; Ectors et al. 1995; Kwon and Kono 1996; Takano et al.…”
Section: Introductionmentioning
confidence: 99%
“…Isolated blastomeres from multicellular embryos still possess developmental capacity in vitro to progress to the blastocyst stage. Successful nuclear transfer in amphibians, fish, sheep, cattle, swine and rabbits have been accomplished by transfer of a blastomere from a pre-implantation stage embryo into an enucleated oocyte with large-scale multiplication achieved by serial repetition of the procedure using blastomeres from nuclear transfer embryos (Willadsen 1986;Ectors et al 1995;Kwon and Kono 1996;Takano et al 1997;Tsunoda and Kato 1998). Modified cloning technique such as serial nuclear transfer, that involved transfer of nuclei from nuclear transferred embryos to an enucleated fertilized zygote, has been shown to increase the developmental competence of amphibian, murine and porcine cloned embryos (Ono et al 2001;Hall et al 2006).…”
Section: Introductionmentioning
confidence: 99%